Commercial Artificial Sweeteners Affect Mice Limb Development: A Morphology and Morphometric Study: Life Sciences-Biology For living things - Qudsi, Fatma Al-; Ahmadi, Abrar Al-; Ganash, Magdah (International Journal of Life Science and Pharma Research, 2021)
Artificial sweeteners are food additives that provide a sweet taste like that of sugar while containing significantly fewer or no calories. The aim of this study was to evaluate the effect of commercial artificial sweeteners on mouse limb development. Adult female mice were divided into three groups: control group, vehicle control group and treated group. The treated group received orally 40 mg/kg body weight artificial sweetener solution, while the vehicle control group received distilled water. The groups were left to mate with normal untreated male mice. On confirmed conception, pregnant females were separated from males. The dose was orally given to the test group before mating, throughout the gestational period till three weeks after giving birth. Foetuses E14.5 and E19.5, were extracted, and newborn and 3 weeks old offspring were examined, and their growth parameters were measured. Congenital malformations were seen in the treated group, such as cerebellar hypertrophy, an increase in the number of forelimbs, atrophy in the lower limb. In some embryos, the amniotic membrane was adherent to the embryo with a very low amount of amniotic fluid. Bone malformation was clearly seen in 1-week offspring, as basic forelimb and hind limb bones were missing. The results of this study showed that there was significant growth retardation in E14.5 and newborns. While in E19.5- and week 3 offspring, there was a significant growth increase (increase in weight, body length tail length and tail length to body length ratio). It was concluded that commercial artificial sweeteners altered growth rate during embryonic development and produced bone and limb congenital malformations in mice.